2000
DOI: 10.1086/315319
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Syncytial Virus Infection Induces Expression of the Anti‐Apoptosis GeneIEX‐1Lin Human Respiratory Epithelial Cells

Abstract: By means of differential display reverse-transcriptase polymerase chain reaction, increased expression of the mRNA encoding the anti-apoptosis gene IEX-1L was found in respiratory epithelial cells infected with respiratory syncytial virus (RSV). IEX-1L mRNA expression increased 5-7-fold in RSV-infected cells at 72 h after infection but remained unchanged in cells exposed to irradiated, replication-incompetent RSV. Because IEX-1L is reported to protect cells from apoptosis induced by tumor necrosis factor (TNF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 24 publications
3
44
0
Order By: Relevance
“…Interestingly, it has been reported that human RS virus, which does not encode a V protein, induces expression of GRP 78 (a major indicator of ER stress in A549 cells) and causes cell death (6). However, there are other reports indicating that infection by RS virus does not induce apoptosis (11,50). It has been reported that mutant SV5 containing mutations in the shared N termini of V and P protein (known as CPIϪ virus) accelerates viral gene expression and causes increased cell death, with characteristics of apoptosis (60).…”
Section: Vol 78 2004 Paramyxovirus V Protein and Apoptosis 5075mentioning
confidence: 99%
“…Interestingly, it has been reported that human RS virus, which does not encode a V protein, induces expression of GRP 78 (a major indicator of ER stress in A549 cells) and causes cell death (6). However, there are other reports indicating that infection by RS virus does not induce apoptosis (11,50). It has been reported that mutant SV5 containing mutations in the shared N termini of V and P protein (known as CPIϪ virus) accelerates viral gene expression and causes increased cell death, with characteristics of apoptosis (60).…”
Section: Vol 78 2004 Paramyxovirus V Protein and Apoptosis 5075mentioning
confidence: 99%
“…Bcl2 and p53 binding protein (BBP/53BP2) is a DNA damage-inducible protein which functions to promote apoptosis upon DNA damage (25,26). IEX-1L antideath protein has been recognized as an apoptosis inhibitor involved in NF-B-mediated cell survival (15,16). In contrast, a proapoptotic role of IEX-1 has also been presented (17)(18)(19).…”
Section: Expression Profiling Of Tnf-␣-modulated Nf-b-dependent Genesmentioning
confidence: 99%
“…Among several NF-B-dependent genes, we focused on x-ray-inducible immediate early response factor-1 (IEX-1), which is a unique immediate-early gene that was initially identified following exposure of human squamous carcinoma cells to X-irradiation (14). Recent studies indicate that IEX-1 is implicated in apoptotic signaling and cell cycle control (15)(16)(17)(18)(19)(20)(21)(22). However, IEX-1 appears to exert apparently contradictory effects, depending on the type of cells, stimuli, and its expressed forms.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, RSV infection of HEp‐2 cells induces the antiapoptotic factor IEX‐1L (Domachowske et al. 2000), and inhibition of phosphatidylinositol‐3‐kinase (PI3K) results in more rapid apoptosis via the NF‐ κ B pathway (Thomas et al. 2002).…”
Section: Discussionmentioning
confidence: 99%